An epoxygenase metabolite of arachidonic acid mediates angiotensin II-induced rises in cytosolic calcium in rabbit proximal tubule epithelial cells. - Madhun, Z T (1991)
Previous studies from this and other laboratories have shown that angiotensin II (AII) induces [Ca2+]i transients in proximal tubular epithelium independent of phospholipase C. AII also stimulates formation of 5,6-epoxyeicosatrienoic acid (5,6-EET) from arachidonic acid by a cytochrome P450 epoxygenase and decreases Na+ transport in the same concentration range. Because 5,6-EET mimics AII with regard to Na+ transport, it effects on calcium mobilization were evaluated. [Ca2+]i was measured by video microscopy with the fluorescent indicator fura-2 employing cultured rabbit proximal tubule. AII-induced [Ca2+]i transients were enhanced by arachidonic acid and attenuated by ketoconazole, an inhibitor of cytochrome P450 epoxygenases. Arachidonic acid also elicited a [Ca2+]i transient that was attenuated by ketoconazole. 5,6-EET augmented [Ca2+]i similar to that seen with AII, but was unaffected by ketoconazole. By contrast, the other regioisomers (8,9-, 11,12-, and 14,15-EET) were much less potent. [Ca2+]i transients resulted from influx through verapamil- and nifedipine-sensitive channels. These results suggest a novel mechanism for AII-induced Ca mobilization in proximal tubule involving cytochrome P450-dependent arachidonic acid metabolism and Ca influx through voltage-sensitive channels.